Reply to the Letter to the Editor on “Prolactin is a Key Factor for Nonalcoholic Fatty Liver Disease in Obese Children” - Zhang, Jianwei (Hormone and Metabolic Research, 2024)
Dear Editor,The authors thank the writers 1 of the letter for reviewing and assessing our article 2, “Prolactin is a Key Factor for Nonalcoholic Fatty Liver Disease in Obese Children”. Overall, we agree that possible selection bias must be considered. However, in clinical studies, we found that hyperprolactinemia is mainly caused by pathological and idiopathic hyperprolactinemia. The former includes hypothalamic pituitary lesions (pituitary prolactinoma and empty sella syndrome, etc.), systemic diseases (hypothyroidism, etc.), tumor secretion (ovarian teratoma, etc.), trauma (chest wall trauma, etc.), surgery (artificial abortion, etc.), and drug side effects (antipsychotics, antidepressants, etc.).